Pretreatment process for detecting main elements of sodium ferrite-based ternary positive electrode material

Through the pretreatment method of ball milling and water bath heating, combined with the technology of adding nitric acid or telluric acid to hydrochloric acid, the problems of large sampling volume, uneven heating and solution transfer loss in the prior art are solved, and more efficient and more accurate detection of metal elements is achieved.

CN119756971AActive Publication Date: 2025-04-04SHENZHEN INSPECTION GRP (ZHEJIANG) QUALITY TECH SERVICE CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411537138.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-04
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing pretreatment methods for sodium ferrite-based ternary cathode materials have problems such as excessive sampling volume, uneven heating, and solution transfer loss, resulting in large errors in the detection result and increased consumption.

Method used

The material is crushed by ball milling, heated in a water bath using a colorimetric tube, and added nitric acid or telluric acid to enhance the oxidation of the acid solution, and directly adjust the volume in the colorimetric tube to reduce the solution transfer step.

Benefits of technology

The acid dosage and heating time are reduced, the detection result error is reduced, and the dissolution efficiency and operation convenience are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111838390000061
    Figure BDA0005111838390000061
  • Figure BDA0005111838390000071
    Figure BDA0005111838390000071
Patent Text Reader

Abstract

The invention relates to the field of element detection, in particular to a pretreatment process for detecting main elements of a sodium ferrite-based ternary positive electrode material, which comprises the following steps: S1, ball milling: carrying out ball milling on the sodium ferrite-based ternary positive electrode material in a wet ball mill until the mass of powder with the aperture of-100 meshes accounts for more than 50% of the mass of the sodium ferrite-based ternary positive electrode material, taking powder; s2, sampling: adding the powder obtained in the step S1 into a colorimetric tube, and adding a mixed solution of deionized water, hydrochloric acid and an additive; s3, dissolving: heating the colorimetric tube in the step S2 in a water bath at 70-80 DEG C until the powder is completely dissolved; and S4, dilution: adding deionized water into the colorimetric tube in the step S3 to achieve a constant volume so as to obtain a diluted solution of the sodium ferrite-based ternary positive electrode material. The application has the effects of reducing the use amount of raw materials and reducing the error of a detection result when the sodium ferrite-based ternary positive electrode material is pretreated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of element detection, and in particular to a pre-treatment process for detecting main elements of a sodium ferrite-based ternary positive electrode material. Background Art

[0002] The main elements of sodium ferrite-based ternary positive electrode materials for sodium ion batteries are sodium, nickel, iron and manganese, with the content of a single element as high as 20%. The existing detection technology is based on YS / T 928.4-2013. The pretreatment plan is to take 0.2g of sample in a polytetrafluoroethylene beaker, add 20mL of hydrochloric acid, dissolve it with slight heat, and transfer it to a 200mL volumetric flask after complete dissolution and make up to volume.

[0003] The prior art has many disadvantages. The sampling volume of the prior pretreatment method is 0.2g. The sampling volume is too large, resulting in a high dilution multiple during liquid phase analysis, which results in large errors and increased consumption of hydrochloric acid. When using hydrochloric acid to dissolve the positive electrode material, an electric heating plate is generally used to heat the beaker. The electric heating plate digestion heating is uneven, and the digestion speed varies when digesting multiple samples, which is time-consuming and labor-intensive. When diluting the sample to a fixed volume, the solution needs to be transferred from the beaker to a volumetric flask, and there is a loss in transferring the digestion solution from the beaker. Summary of the invention

[0004] In order to reduce the amount of raw materials used and reduce the error of detection results when pre-treating sodium ferrite-based ternary positive electrode materials, the present application provides a pre-treatment process for detecting main elements of sodium ferrite-based ternary positive electrode materials.

[0005] The pre-treatment process for the detection of main elements of a sodium ferrite-based ternary cathode material provided in this application adopts the following technical solution:

[0006] A pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material comprises the following steps:

[0007] S1. Ball milling: ball mill the sodium ferrite-based ternary positive electrode material in a wet ball mill, screen it with a sieve with an aperture of 100 mesh, and continue to put the remaining particles into the wet ball mill for ball milling until the mass of the powder with an aperture of -100 mesh accounts for more than 50% of the sodium ferrite-based ternary positive electrode material, and take the powder;

[0008] S2, sampling: take the powder obtained in step S1 and put it into a colorimetric tube, and add a mixed solution of deionized water, hydrochloric acid and additives;

[0009] S3, dissolving: heating the colorimetric tube in step S2 in a water bath at 70-80°C until the powder is completely dissolved;

[0010] S4, dilution: adding deionized water to the colorimetric tube in step S3 to make up the volume, to obtain a diluted solution of the sodium ferrite-based ternary positive electrode material;

[0011] The additive in step S2 is one or a combination of nitric acid and telluric acid, the additive in step S2 is one or a combination of nitric acid and telluric acid, the additive in step S2 is one or a combination of nitric acid and telluric acid, the concentration of hydrochloric acid is 36-38wt%, the concentration of nitric acid is 65-70wt%, and the concentration of telluric acid is 25-30wt%.

[0012] By adopting the above technical scheme, the current basis for the detection of metal element content in sodium ferrite-based ternary positive electrode materials for sodium ion batteries is YS / T 928.4-2013. The pretreatment scheme for positive electrode materials in this standard is to take 0.2g of sample in a polytetrafluoroethylene beaker, add 20mL of hydrochloric acid, dissolve it with slight heat, transfer it to a 200mL volumetric flask after complete dissolution, and fix the volume. However, this scheme has many problems in actual operation:

[0013] First, hydrochloric acid is used to dissolve metal elements in the prior art. Hydrochloric acid mainly relies on its acidity to dissolve metal materials, so that when dissolving metal materials, not only is the amount of hydrochloric acid used large, but the dissolution efficiency is also low. In the present application, by adding nitric acid or telluric acid to hydrochloric acid, the oxidizing property of the acid solution is greatly improved, so that the acid solution of equal concentration can dissolve more metal materials, reducing the amount of acid used;

[0014] Second, in the prior art, the beaker is heated by a heating plate. This heating method heats the solution in the beaker unevenly during heating, so that it takes a long time for the acid solution to completely dissolve the metal material. In the present application, a water bath is used to heat the colorimetric tube, which can heat the entire colorimetric tube, resulting in a more uniform heating effect and shortening the time it takes for the acid solution to dissolve the metal material.

[0015] Third, in the prior art, when preparing the sample for injection, the solution in the beaker needs to be transferred to a volumetric flask for volume adjustment. However, in the process of transferring the solution, the solution is easily lost or even contaminated, resulting in an increase in the error of the test result. In the present application, the volume adjustment step is performed directly in the colorimetric tube, which reduces the solution transfer step, reduces the occurrence of solution loss during transfer, and reduces the error of the final test result.

[0016] Optionally, in step S3, before heating the colorimetric tube to 70-80° C., the following steps are further performed:

[0017] S31. Open the cap of the colorimetric tube and heat it in a water bath at 30-50°C for 4-6 minutes.

[0018] By adopting the above technical scheme, when the nitric acid solution is directly heated to a higher temperature, the nitric acid is easily decomposed, so that the concentration of the acid solution decreases, and more acid needs to be added to dissolve the metal material. In the present application, a gradual heating method is adopted, and the colorimetric tube is first preheated at a lower temperature, and then heated to the target temperature for dissolution, which effectively reduces the decomposition of nitric acid and reduces the amount of nitric acid used.

[0019] Optionally, in step S4, before adding deionized water to the colorimetric tube to make up the volume, the following steps are further performed:

[0020] S41, placing the colorimetric tube in step S3 in a fume hood and cooling it to room temperature;

[0021] S42, observe whether the colorimetric tube is completely dissolved. If not, continue to add a mixed solution of deionized water, hydrochloric acid and nitric acid, and repeat steps S31, S3 and S41.

[0022] By adopting the above technical solution, in the present application, the method of first cooling and then preparing samples is adopted to reduce the error caused by temperature changes. Since the temperature drop may cause the solute to precipitate, the method of repeated acid dissolution is adopted to prevent the metal material from precipitating at room temperature.

[0023] Optionally, the amount of powder used in step S2 is 0.1-0.2 g.

[0024] By adopting the above technical solution, the general amount of metal material used in the prior art is 0.2g. In this application, the experimental error is reduced by improving the process, so that there is no need to reduce the error by increasing the amount of raw materials when preparing samples, so the amount of raw materials used is less.

[0025] Optionally, the additive in step S2 is telluric acid.

[0026] By adopting the above technical solution, in the present application solution, the chloride ions of hydrochloric acid form complex ions with metal elements, thereby reducing the difficulty of oxidizing acids dissolving metal elements. Through multiple experiments by operators, it was found that using telluric acid instead of nitric acid still has a good dissolution effect.

[0027] Optionally, in step S2, the volume ratio of deionized water, hydrochloric acid and additive is 2:(0.5-1):(1.5-3).

[0028] By adopting the above technical solution, operators have found through multiple experiments that when the volume ratio of deionized water, hydrochloric acid and additives is 2: (0.5-1): (1.5-3), the dissolution effect on metal elements is better.

[0029] Optionally, the solid-liquid ratio of the powder to the mixed solution in step S2 is 1 gram: (50-100) milliliters.

[0030] By adopting the above technical solution, in the present application, the amount of acid used is significantly reduced by improving the acid solution formula.

[0031] Optionally, the solid-to-liquid ratio of the powder in step S2 to the solution after volume adjustment in step S4 is 1 gram: (250-1000) milliliters.

[0032] By adopting the above technical solution, in the present application, since a colorimetric tube is used as a constant volume container, the colorimetric tube itself has a scale, and sample solutions of different concentrations can be easily configured, making the operation more convenient.

[0033] In summary, the present application includes at least one of the following beneficial technical effects:

[0034] 1. By adding nitric acid or telluric acid to hydrochloric acid, the oxidizing property of the acid solution is greatly improved, so that the acid solution of equal concentration can dissolve more metal materials and reduce the amount of acid used;

[0035] 2. The present application adopts a water bath heating method for the colorimetric tube, which can heat the entire colorimetric tube, making the heating effect more uniform and shortening the time for the acid solution to dissolve the metal material;

[0036] 3. In the present application, the volume determination step is performed directly in the colorimetric tube, which reduces the steps of solution transfer, reduces the occurrence of solution loss during solution transfer, and reduces the error in the final test result. DETAILED DESCRIPTION

[0037] The present invention is further described below through specific implementation modes, but the protection scope of the present invention is not limited thereto.

[0038] Preparation of positive electrode material powder: Take 10g of iron-based sodium ternary positive electrode material (prepared by existing technology, the theoretically calculated manganese content in the positive electrode material is 16.43%, the iron content is 16.70%, and the nickel content is 17.55%), ball mill it in a wet ball mill, use a sieve with an aperture of 100 mesh for screening, and continue to put the remaining particles into the wet ball mill for ball milling until the mass of the powder with an aperture of -100 mesh accounts for more than 50% of the sodium ferrite-based ternary positive electrode material.

[0039] Example 1: Take 0.1g of powder and add it into a colorimetric tube, add a mixed solution of 2ml of deionized water, 1ml of hydrochloric acid and 3ml of nitric acid, first heat it in a water bath at 30-50℃ for 5 minutes, then heat it in a water bath at 70-80℃ until the powder is completely dissolved, place the colorimetric tube in a fume hood and cool to room temperature, no precipitation is precipitated, add deionized water to make up to 50ml.

[0040] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses the prior art to pre-treat the positive electrode material, and the steps are as follows:

[0041] Take 0.2g of powder into a polytetrafluoroethylene beaker, add 20mL of hydrochloric acid, dissolve under slight heat, and after complete dissolution, transfer to a 200mL volumetric flask and make up to volume.

[0042] The difference between Example 2 and Example 1 is that the additive used in Example 2 is telluric acid.

[0043] Example 3: Take 0.2g of powder and add it into a colorimetric tube, add a mixed solution of 2ml of deionized water, 1ml of hydrochloric acid and 3ml of telluric acid, first heat it in a water bath at 30-50℃ for 5 minutes, then heat it in a water bath at 70-80℃ until the powder is completely dissolved, place the colorimetric tube in a fume hood and cool to room temperature, if no precipitate is formed, add deionized water to make up to 50ml.

[0044] Example 4: Take 0.2g of powder and add it to a colorimetric tube, add a mixed solution of 2ml of deionized water, 1ml of hydrochloric acid and 3ml of nitric acid, first heat it in a water bath at 30-50℃ for 5 minutes, then heat it in a water bath at 70-80℃. If it is not completely dissolved, add 1ml of a mixed solution of deionized water, hydrochloric acid and nitric acid in a ratio of 2:1:3, first heat it in a water bath at 30-50℃ for 5 minutes, then heat it in a water bath at 70-80℃. The powder is completely dissolved, the colorimetric tube is placed in a fume hood and cooled to room temperature. No precipitate is precipitated, and deionized water is added to make up to 50ml.

[0045] The difference between Examples 5 and 6 and Example 2 is that the volumes after constant volume in step S4 are different, as shown in the following table:

[0046] Example 2 Example 5 Example 6 Volume(ml) 50 20 100

[0047] Example 7: Take 0.1g of powder and add it to a colorimetric tube, add 6ml of mixed solution (the volume ratio of deionized water, hydrochloric acid and telluric acid is 4:1:3), first heat it in a water bath at 30-50℃ for 5 minutes, and then heat it in a water bath at 70-80℃ until the powder is completely dissolved, add 2ml of a mixed solution of deionized water, hydrochloric acid and nitric acid in a ratio of 4:1:3, first heat it in a water bath at 30-50℃ for 5 minutes, and then heat it in a water bath at 70-80℃ until the powder is completely dissolved, place the colorimetric tube in a fume hood and cool to room temperature, no precipitate is precipitated, add deionized water to make up to 50ml.

[0048] Comparative Example 2: Take 0.1g of powder and add it to a colorimetric tube, add 6ml of mixed solution (the volume ratio of deionized water, hydrochloric acid and telluric acid is 8:1:3), first heat it in a water bath at 30-50℃ for 5 minutes, and then heat it in a water bath at 70-80℃ until the powder is not completely dissolved, add 2ml of a mixed solution of deionized water, hydrochloric acid and nitric acid in a ratio of 8:1:3, first heat it in a water bath at 30-50℃ for 5 minutes, and then heat it in a water bath at 70-80℃, if it is not completely dissolved, repeat several times until the powder is completely dissolved. Compared with Example 2, the final additional volume of the mixed solution added is 6ml, the colorimetric tube is placed in a fume hood to cool to room temperature, no precipitate is precipitated, and deionized water is added to make the volume 50ml.

[0049] Comparative Examples 3 and 4 are repeated tests of Example 1.

[0050] Comparative Examples 5 and 6 are repeated tests of Example 2.

[0051] Comparative Examples 7 and 8 are repeated tests of Comparative Example 1.

[0052] In the above embodiments and comparative examples, the concentration of hydrochloric acid is 37wt%, the concentration of nitric acid is 65wt%, and the concentration of telluric acid is 25wt%.

[0053] Detection method:

[0054] Nickel chloride solutions were prepared according to a concentration gradient of 0.1, 0.2, 0.3, 0.4, and 0.5 g / l and liquid phase analysis was performed to obtain a nickel chloride standard curve;

[0055] Ferric chloride solutions were prepared according to a concentration gradient of 0.1, 0.2, 0.3, 0.4, and 0.5 g / l and liquid phase analysis was performed to obtain a ferric chloride standard curve;

[0056] Manganese chloride solutions were prepared according to concentration gradients of 0.1, 0.2, 0.3, 0.4, and 0.5 g / l and liquid phase analysis was performed to obtain a manganese chloride standard curve;

[0057] The final solution of each embodiment and comparative example was sampled and subjected to liquid phase analysis to obtain the peak area of ​​each metal element in each embodiment and comparative example and compare it with the standard curve to obtain the content of nickel, iron and manganese elements.

[0058] The test results are as follows:

[0059] Conclusion: Through the experimental process of Example 1 and Comparative Example 1, it can be seen that when the present application performs pre-treatment on metal materials, only 6 ml of acid solution is needed to process 0.1 g of metal sample, which is significantly reduced compared with 20 ml in the prior art.

[0060] Heating time (min) Example 1 15 Comparative Example 1 25

[0061] Conclusion: It can be seen from the heating time of Example 1 and Comparative Example 1 in the above table that, compared with the prior art, the present application significantly shortens the time spent on heating and dissolving the metal material, thereby improving efficiency and reducing energy consumption. This is because, compared with heating with an electric heating plate, the water bath heating colorimetric tube can heat the entire colorimetric tube, resulting in a more uniform heating effect and shortening the time it takes for the acid solution to dissolve the metal material.

[0062] Example 1 Comparative Example 1 Iron content (g / l) 0.3320 0.3318 Iron element error (%) 0.599 0.659 Nickel content (g / l) 0.3489 0.3487 Nickel element error (%) 0.598 0.655 Manganese content (g / l) 0.3266 0.3264 Manganese element error (%) 0.609 0.67

[0063] Conclusion: Through the data of Example 1 and Comparative Example 1 in the above table (the element error in the table is calculated compared with the theoretical concentration of the sample solution), it can be seen that the sample content of the positive electrode material prepared in the present application is higher than the sample of the positive electrode material prepared by the prior art. At the same time, the content of each metal element in the sample of the positive electrode material prepared in the present application is smaller than that of the sample of the positive electrode material prepared by the prior art, and is closer to the theoretical data. This is because in the present application, the volume fixing step is carried out directly in the colorimetric tube, which reduces the step of solution transfer, reduces the occurrence of solution loss during solution transfer, and reduces the error of the final test result.

[0064] Example 1 Example 2 Example 3 Iron content (g / l) 0.3320 0.3322 0.6643 Iron element error (%) 0.599 0.539 0.554 Nickel content (g / l) 0.3489 0.3491 0.6982 Nickel element error (%) 0.598 0.541 0.541 Manganese content (g / l) 0.3266 0.3268 0.6537 Manganese element error (%) 0.609 0.548 0.533

[0065] Conclusion: Through the data of Example 1, Example 2 and Example 3 in the above table (the element error in the table is calculated compared with the theoretical concentration of the sample solution), it can be seen that in the present application, the additives selected from nitric acid and telluric acid have good pre-treatment effects, but the oxidation product of nitric acid is gas, while the oxidation product of telluric acid is solute and remains in the sample, which reduces the generation of toxic and harmful gases and is more suitable for the current green production requirements.

[0066] Conclusion: Through the test process of Example 1 and Example 2, Example 3 and Example 4, it is found that after using telluric acid instead of nitric acid, the acid solution has a stronger dissolution effect on the metal positive electrode material. Therefore, in this application, the additive of the acid solution is preferably telluric acid.

[0067] Conclusion: Through the test process of Examples 2, 7 and Comparative Example 2, it can be seen that the volume ratio of deionized water, hydrochloric acid and additives in step S2 of the present application is more suitable at 2: (0.5-1): (1.5-3). When the proportion of water is too high, the acid concentration is low, the volume of acid solution required to dissolve the metal material is large, and the operation is more troublesome.

[0068] Example 2 Example 5 Example 6 Iron content (g / l) 0.3322 0.8304 0.1661 Iron element error (%) 0.539 0.551 0.539 Nickel content (g / l) 0.3491 0.8728 0.1745 Nickel element error (%) 0.541 0.536 0.57 Manganese content (g / l) 0.3268 0.8169 0.1634 Manganese element error (%) 0.548 0.56 0.548

[0069] Conclusion: From the data of Examples 2, 5 and 6 in the above table (the element error in the table is calculated compared with the theoretical concentration of the sample solution), it can be seen that the concentration values ​​of the metal sample solutions prepared in the present application at different concentrations are close to the theoretical values, and the errors are small, indicating that using a colorimetric tube as a constant volume container, sample solutions of different concentrations can be easily configured, and the operation is more convenient.

[0070]

[0071]

[0072] Conclusion: It can be seen from the data in the above table that compared with the traditional process, the addition of nitric acid or telluric acid to hydrochloric acid in this application significantly reduces the error of the test results. At the same time, the test results are more stable under repeated tests.

[0073] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A pretreatment process for detecting main elements of sodium ferrite-based ternary cathode materials, characterized in that: The steps include: S1. Ball milling: ball mill the sodium ferrite-based ternary positive electrode material in a wet ball mill, screen it with a sieve with an aperture of 100 mesh, and continue to put the remaining particles into the wet ball mill for ball milling until the mass of the powder with an aperture of -100 mesh accounts for more than 50% of the sodium ferrite-based ternary positive electrode material, and take the powder; S2, sampling: take the powder obtained in step S1 and put it into a colorimetric tube, and add a mixed solution of deionized water, hydrochloric acid and additives; S3, dissolving: heating the colorimetric tube in step S2 in a water bath at 70-80°C until the powder is completely dissolved; S4, dilution: adding deionized water to the colorimetric tube in step S3 to make up the volume, to obtain a diluted solution of the sodium ferrite-based ternary positive electrode material; The additive in step S2 is one or a combination of nitric acid and telluric acid, the concentration of hydrochloric acid is 36-38wt%, the concentration of nitric acid is 65-70wt%, and the concentration of telluric acid is 25-30wt%.

2. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 1, characterized in that: In step S3, before heating the colorimetric tube to 70-80° C., the following steps are further performed: S31. Open the cap of the colorimetric tube and heat it in a water bath at 30-50°C for 4-6 minutes.

3. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 2, characterized in that: In step S4, the following steps are further performed before adding deionized water to the colorimetric tube to make it constant: S41, placing the colorimetric tube in step S3 in a fume hood and cooling it to room temperature; S42, observe whether the colorimetric tube is completely dissolved. If not, continue to add a mixed solution of deionized water, hydrochloric acid and nitric acid, and repeat steps S31, S3 and S41.

4. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 1, characterized in that: The amount of powder used in step S2 is 0.1-0.2 g.

5. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 1, characterized in that: The additive in step S2 is telluric acid.

6. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 1, characterized in that: In step S2, the volume ratio of deionized water, hydrochloric acid and additive is 2:(0.5-1):(1.5-3).

7. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 1, characterized in that: The solid-liquid ratio of the powder to the mixed solution in step S2 is 1 gram: (50-100) milliliters.

8. The pretreatment process for detecting main elements of a sodium ferrite-based ternary cathode material according to claim 1, characterized in that: The solid-to-liquid ratio of the powder in step S2 to the solution after volume adjustment in step S4 is 1 gram: (250-1000) milliliters.

Citation Information

Patent Citations

  • Method for measuring trace elements of aluminum, chromium, copper, manganese, nickel and silicon in pure iron

    CN107764802A

  • Method for testing main element content of sodium ion battery positive electrode material

    CN116203008A

  • ICP-OES (Inductively Coupled Plasma-Optical Emission Spectrometer) analysis method for determining sodium in ternary positive electrode material

    CN117929358A

  • Method for detecting main element content of lithium manganese iron phosphate

    CN117969492A